Sexual dimorphism of sulcal morphology of the ferret cerebrum revealed by MRI-based sulcal surface morphometry - Sawada, Kazuhiko; Horiuchi-Hirose, Miwa; Saito, Shigeyoshi; Aoki, Ichio (Frontiers in Neuroanatomy, 2015)
The present study quantitatively assessed sexual dimorphism of cortical convolution and sulcal morphology in young adult ferrets by MRI-based sulcal surface morphometry. Ex vivo T1-weighted (short TR/TE) MRI of the ferret cerebrum was acquired with high spatial resolution at 7-tesla. The degree of cortical convolution, evaluated quantitatively based on 3D MRI data by sulcation index (SI), was significantly greater in males (0.553±0.036) than in females (0.502±0.043) (p < 0.001). The rostrocaudal distribution of the cortical convolution revealed a greater convolution in the frontal region of the cortex in males than in females and by a posterior extension of the convolution in the temporo-parieto-occipital region of males. Although the cerebral width in the frontal region was not different between sexes, the rhinal fissure and rostral region of splenial sulcus were more infolded in males than in females. On the contrary, the cerebral width was greater in males in the temporo-parieto-occipital region, and male-prominent posterior extension of infolding was noted in the lateral sulcus, caudal suprasylvian sulcus, pesudosylvian sulcus, hippocampal sulcus and the caudal region of splenial sulcus. Notably, the caudal descending region of lateral sulcus was clearly infolded in males, but obscured in females. The present results suggest a region-related sexual dimorphism of the sulcal infolding, which is reflected by local cortical expansion in the ferret cerebrum. In particular, male-favored sulcal infolding with expansion of the temporo-parieto-occipital neocortex may be relevant to the human cerebral cortex regarding visuo-spatial and emotion processing, which are known to differ between sexes. The present results will provide fundamental information assessing sex-related changes in the regional sulcal infolding, when ferrets with experimentally-induced gyrification abnormality will be used as models for male-prevalent or male-earlier-onset neurodevelopmental disorders.